Don Álvaro, or, The force of fate (1835) : a play by Ángel de Saavedra, Duke of Rivas ; translated from the Spanish by Robert M. Fedorchek ; introduction by Joyce Tolliver. - Rivas, Angel de Saavedra, duque de, 1791-1865 (Catholic University of America Press, 2005)
Don Alvaro, or the Force of Fate by Angel de Saavedra, Duke of Rivas (1791-1865), premiered in 1835 in Madrid and changed the Spanish stage forever after. It was the benchmark Romantic play of early nineteenth-century Spain. In this English edition designed for either classroom use or performance, Robert Fedorchek presents a readable translation faithful to the tone and spirit of the original. Joyce Tolliver enhances the book with a rich introduction highlighting the work's lasting significance. The play tells of the torrid love of the mysterious Don Alvaro and the lovely Dona Leonor, and how fate intervenes - by way of Alvaro's role in the ""accidental"" death of Leonor's father - to bring about the extermination of Leonor's family at the hands of the man who loves her to distraction. Although chronologically not the first Spanish Romantic drama, Don Alvaro is generally considered the true exponent of the freedom of expression that Romanticism brought to the theater. It does away with all the Neoclassical rules: it exceeds twenty-four hours; the action takes place in two countries; it mixes high and low; prose alternates with verse; and the characters express, melodramatically and passionately, their innermost feelings. It is also generally considered the first play in the best trilogy, along with Antonio Garcia Gutierrez's El trovador (The troubadour, 1836) and Juan Eugenio Hartzenbusch's Los amantes de Teruel (The lovers of Teruel, 1837)